An update of Wnt signalling in endometrial cancer and its potential as a therapeutic target. Issue 12 (December 2018) - Coopes, A; Henry, C E; Llamosas, E; Ford, C E
Abstract : Endometrial cancer is the most common gynaecological malignancy in developed nations, and its prevalence is rising as women defer or decide not to have children and as obesity rises, both key risk factors. Despite this, treatment options remain limited, particularly for advanced or refractory disease. New genomic analyses have revealed distinct mutational profiles with therapeutic and prognostic potential. Wnt signalling, which is pivotal in embryogenesis, healing and homeostasis, is of importance in the endometrium and has been linked to carcinogenesis. This review aims to update and discuss the current evidence for the role of β-catenin dependent and independent Wnt signalling, including the ROR receptors in the endometrium and its potential as a therapeutic target, in light of recent trials of Wnt-targeted therapy in multiple tumour types.